Comparing the effects of meal replacements with an isocaloric reduced‐fat diet on nutrient intake and lower urinary tract symptoms in obese men. Issue 3 (20th September 2013) - Khoo, J.; Ling, P.‐S.; Chen, R. Y.‐T.; Ng, K.‐K.; Tay, T.‐L.; Tan, E.; Cho, L.‐W.; Cheong, M.
Abstract Background Lower urinary tract symptoms (LUTS) in men are associated with obesity, particularly central obesity as measured by waist circumference (WC), and may improve with weight loss. We aimed to compare effects of a meal‐replacement based diet with isocaloric reduced‐fat plan on LUTS and nutrient intake in obese Asian men. Methods Obese Asian [mean (range) body mass index of 32.9 (30.5–42.3) kg m–2] men [mean (range) age 40.2 (30–61) years] were randomised to a reduced‐fat (< 30% of energy) diet [conventional reduced‐fat diet (CD) group; n = 23] or meal‐replacement‐based plan [meal replacement (MR) group; n = 23], to reduce daily intake by 2000 kJ for 12 weeks. Results CD and MR groups had statistically significant and similar reductions in weight (−2.6 ± 1.9 kg versus −4.2 ± 3.8 kg), overall LUTS severity measured with International Prostate Symptom Scale (IPSS) scores (−1.71 ± 1.93 points versus −2.42 ± 2.12 points) and insulin resistance [homeostasis model assessment (HOMA) calculated from plasma glucose and insulin]. The MR group had significantly greater decreases in WC (−4.8 ± 3.3 cm versus −2.5 ± 2.3 cm), fat mass (−2.47 ± 3.63 kg versus −1.59 ± 2.32 kg), fat intake, plasma C‐reactive protein, and in storage LUTS score (−1.59 ± 1.33 points versus −1.00 ± 0.87 points), which was associated with a decreased fat intake (r = 0.48, P = 0.03). A decrease in overall IPSS score was associated with reductions in weight, WC and HOMA. Conclusions Weight loss as a result of CD or MR had similar efficacy in relieving LUTS. MR produced greater reductions in fat intake, adiposity and storage LUTS.